دراسة تحليلية إحصائية للآثار الاقتصادية للضرائب والرسوم في سورية خلال الفترة (1990-2009) - النعيمي, قاسم; العدي, إبراهيم; رجوب, ابتسام علي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تناول هذا البحث الآثار الاقتصادية للضرائب والرسوم في سورية بوصفه دراسة تحليلية إحصائية خلال الفترة 1990-2009 انطلاقاً من بيانات المجموعة الإحصائية السنوية الصادرة عن المكتب المركزي للإحصاء، وباستخدام البرنامج الإحصائي SPSS قمنا ببناء نماذج قياسية صالحة لتقدير معلمات نماذج أثر الضريبة على كل من الاستثمار العام، الاستثمار الخاص، إجمالي التكوين الرأسمالي، الاستهلاك. كما يمكن استخدام هذه النماذج في عملية التنبؤ لهذه المتغيرات. هذا وقد توصلنا إلى مجموعة من النتائج المهمة من بينها وجود علاقة طردية وقوية بين الضريبة ومجمل تكوين رأس المال الثابت في كل من القطاعين العام الخاص، إلا أن الضريبة في الحقيقة لم تكن أداة فعالة في زيادة معدل نمو كل من الاستثمار العام والخاص. كما تبين لنا أن النظام الضريبي السوري يعتمد على الضرائب غير المباشرة (ضرائب الاستهلاك) التي تخفض من استهلاك الأفراد مما يسهم في انخفاض حجم العمالة والدخل القومي. بالإضافة إلى ذلك، تراجع كبير في عدالة توزيع الدخل القومي في سورية بسبب ارتفاع الضرائب غير المباشرة التي أثرت بشكل كبير على فئة ذوي الدخل المحدود، هذا وقد تبين لنا ذلك من خلال منحنى لورانس. This research handles the economic effects of taxes and fees presented as a statistical and analytical study during the period 1990-2009 in Syria. It was based on the annual statistical data issued by the Central Bureau of Statistics. Using the statistic programme (SPSS) we have made econometric models to estimate the parameters of models of the impact of the tax on all public investment, private investment, gross capital formation, consumption, and these models can be used in the prediction of these variables, We have reached many important results, among which, the clear centrifugal relationship between taxes and total fixed capital formation in both public and private sectors. In fact, the tax itself had not been an effective tool in increasing the rate of growth of both public and private investment. It also shows us that the Syrian tax system depends on indirect taxes (consumption tax) that reduce the consumption of individuals contributing to the decline in the volume of employment and national income, In addition to the significant decline in distributing the national income fairly due to high indirect taxes which consequently affected the low-income category, Show us through the curve of Lawrence.